2016
DOI: 10.3171/2015.3.spine14997
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative posterior lumbar muscle changes and their relationship to segmental motion preservation or restriction: a randomized prospective study

Abstract: OBJECT To date, it remains unclear whether the preservation of segmental motion by total disc replacement (TDR) or motion restriction by stand-alone anterior lumbar interbody fusion (ALIF) have an influence on postoperative degeneration of the posterior paraspinal muscles or the associated clinical results. Therefore, the purpose of the present prospective randomized study was to evaluate the clinical parameters and 3D quantitative radiological changes in the paraspi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…Alternatively, in cases where conservative treatment has failed or in those with concurrent spinal stenosis or radiculopathy, surgical management may be considered [8]. At present, there is some evidence to suggest that changes in the morphology of multifidus following a surgical procedure are associated with worse clinical outcomes, although the magnitude of this effect is unclear [10][11][12][13][14]. Furthermore, the association between the pre-operative morphological condition of multifidus and post-operative clinical outcomes is not well described [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, in cases where conservative treatment has failed or in those with concurrent spinal stenosis or radiculopathy, surgical management may be considered [8]. At present, there is some evidence to suggest that changes in the morphology of multifidus following a surgical procedure are associated with worse clinical outcomes, although the magnitude of this effect is unclear [10][11][12][13][14]. Furthermore, the association between the pre-operative morphological condition of multifidus and post-operative clinical outcomes is not well described [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al [23] demonstrated that FCSA assessed by CT is an acceptable method for evaluating paraspinal muscle atrophy, with a high consistency of 0.794 in the intraclass correlation between CT and MRI. Many studies have reported a decrease in the adjacent FCSA, ranging from − 2 to − 38% using an open approach, compared with + 9.9% to − 12.2% using minimally invasive techniques [17,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Second, paravertebral muscles are damaged, and muscle strength is reduced, which may accelerate the instability of adjacent segments. Strube et al [26] reported that the overall atrophy and fatty degeneration ratio at the adjacent segments after the anterioronly treatment option (ALIF) appears to be rather low.…”
Section: Discussionmentioning
confidence: 99%
“…This is why the posterior elements and ligaments are important in the maintenance of spinal stability. It has been established that posterior spinal surgery damages the paraspinal musculature, facet joint, and ligaments, causing limitations of ROM 9,17) . Thus, in clinical practice, postoperative posterior lumbar muscle damage plays an important role in the limitations of ROM.…”
Section: Discussionmentioning
confidence: 99%